A SCOPING REVIEW: IMPACT OF MALARIA IN PREGNANCY - Harlinda Widia Putri; Herlin Fitriana Kurniawati; Ismarwati Ismarwati (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Based on world malaria reports, the most malaria cases are in the African region, followed by the Eastern Mediterranean region and Southeast Asia region. Twenty-nine countries account for global malaria cases. In the Asia-Pacific region, the rate of malaria transmission is relatively low when compared to sub-Saharan Africa, but it is basically the same as the malaria problem in Africa because the harmful effects of malaria in various regions remain the same. The process of pregnancy can aggravate malaria cases; pregnant women suffering from malaria will affect the process of pregnancy and the fetus and baby born. This Scoping Review aims to synthesize research evidence and categorize research articles on the impact of malaria on pregnant women and their babies in Asia-Pacific countries. Literature search was carried out using the PRISMA flowchart guidelines which were applied to present the article search flow. The synthesis shows 11 articles obtained from the search process. This review raises 6 themes, namely: anemia, low birth weight, premature birth, malaria in infants, placental malaria, and primigravida. The impact of malaria in pregnancy that most often occurs in pregnant women is anemia, low birth weight, premature birth, placental malaria, and malaria in infants.